Reinforcement of poly (methyl methacrylate) by WS2 nanotubes towards antiballistic applications. (3rd May 2021) - Ghosh, Saptarshi; Otorgust, Gilad; Idelevich, Alexander; Regev, Omri; Lapsker, Igor; Lewitus, Dan Y.; Zak, Alla
Abstract: Tungsten disulfide nanotubes (INT-WS2 ) have been implemented as reinforcing and antiballistic agent in PMMA (poly(methyl methacrylate)) matrix. The performance of the native polymer through addition of INT-WS2 was characterized by the dynamic mechanical analysis (DMA), split-Hopkinson pressure bar (SHPB), flexural, tensile and impact tests. The composites were prepared by a twin screw extruder via optimizing extrusion parameters, INTs concentrations, with and without usage of compatibilizer. Under the best conditions, these nancomposites exhibited homogeneous dispersion with average increase of 39% for the flexural strength accompanied by 83% enhancement in strain at break, compared to pristine. In tensile test an improvement of ~13% for the tensile strength and of 25% in elongation at break were achieved. Impact strength of the composite was also improved by 23% compared to the neat polymer, which is at par or even superior to existing fillers for PMMA. These results demonstrate improvement in the impact resistance without compromising the elastic domain. In the SHPB test, an average enhancement of 31% in the energy absorption capacity (toughness) and of 43% in elongation at break, compared to neat PMMA, were observed. The reinforcing mechanism of INT-WS2 was attributed to homogeneous distribution and alignment of nanotubes in the molded samples. Graphical abstract: Image 1